Prevalence and Factors Determining Adolescents Risk Taking Behaviours in Sarawak, Malaysia - Ying, Khung Ying; Md Mizanur, Rahman; Andrew, Kiyu (International Islamic University Malaysia, 2024)
INTRODUCTION: During adolescence, significant physical, emotional, and social changes influence growth. This phase exposes adolescents to risky situations. Understanding adolescent risk-taking is crucial. This study aims to determine the extent of risk-taking behaviour among Malaysian adolescents and identify associated factors. MATERIALS AND METHODS: In a community-based study, we surveyed 1,344 Malaysian adolescents aged 10-19 across 22 districts in Sarawak using multi-stage cluster sampling and face-to-face interviews. Data analysis was performed with IBM SPSS v28.0. RESULTS: Analysis found that 43.7% of adolescents engaged in risky behaviours, with a higher incidence in males (50.1%) compared to females (37.4%). Multinomial logistic regression analysis identified for low-medium risk behaviours were being aged 15-19 (AOR=1.52; CI:1.14-2.02), infrequent religious practice (AOR=1.70; CI:1.01-2.84), poor parent-child relations (AOR=2.02; CI:1.07-3.83) and having a history of mental abuse (AOR=3.02; CI:1.37-6.62). However, a larger family size appeared to be a protective factor (AOR=0.39; CI: 0.18-0.89). High-risk behaviours were more prevalent in older (AOR=2.65; CI:1.91, 3.68) male adolescents (AOR=2.75; CI: 2.02, 3.75) and low religious value (AOR=3.55; CI: 1.32-9.52), larger families (AOR=2.03; CI: 1.38-3.00), lower school grades (AOR=1.74; CI: 1.27-2.38), physical ailments (AOR=2.63; CI:1.60-4.32), and a history of mental abuse (AOR=3.85; CI:1.78-8.31). CONCLUSION: Adolescents aged 15-19 with weak family ties, low religious engagement, and a history of mental abuse tend to exhibit low to medium risk behaviours. Older male adolescents with health issues are more likely to engage in high-risk behaviours, whereas those from larger families show fewer such tendencies. These insights are crucial for shaping targeted interventions and policies.